The black stallion's blood bay colt - Farley, Walter, 1915-1989 (Farley, Walter, 1915-1989. Black stallion series., 1994)
A boy is entrusted to attend the birth, train, and drive a blood bay colt that is the great hope of an aging reinsman who refuses to be reconciled to the fact that sulky-racing has moved from the county fair to the big night time, moneymaking raceways.